Vocabulary Acquisition through Self-Regulated Learning on Speaking and Writing Development - Budi Waluyo (International Journal of Language Teaching and Education, 2018)
Despite the crucial role of vocabulary in foreign language acquisition, little is known about its influence on speaking and writing development from self-regulated learning concept. Thus, by employing a path analysis, this study examines the influence of vocabulary acquisition through self-regulated learning on beginner (N = 215) and intermediate (N = 195) students’ speaking and writing development at Walailak University, Thailand. The findings suggest significant paths from vocabulary acquisition to students’ speaking and writing development, but noting the influence of proficiency level. These findings contribute to the development of research in vocabulary acquisition and self-regulated learning with regards to speaking and writing development.